PERAN GURU DALAM PENGUATAN KARAKTER PESERTA DIDIK - Sarpendi; Ahmad Sayuti; Budi Waluyo (UNISAN JURNAL, 2024)
Character values ​​are plus character, which involves knowledge, feelings and actions. Without these three aspects the character will not be effective. Thus the character that is applied systematically and continuously, a child will become emotionally intelligent. This intelligence is an important provision in preparing children to meet the future, because someone will more easily and successfully face all kinds of challenges to succeed academically. Therefore, a nation will feel threatened with extinction if the morality of the next generation is bleak. The teacher is the best example in education, has a professional character who has the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students or students. In the context of achieving the goals of character education, the teacher is the spearhead of this success. The question of this research is how is the role of the moral aqidah teacher in strengthening the character of the eighth grade students of Madrasah Tsanawiyah Raden Fatah, Rambang Niru District, Muara Enim Regency?. The purpose of this study was to determine and analyze the role of the moral aqidah teacher in strengthening the character of the eighth grade students. This research is descriptive qualitative. Data was collected by means of interviews, observation, and documentation. Based on the results of the study, it can be concluded that the role of the teacher of moral aqidah is in strengthening the character of students by using methods of habituation, example, advice, rewards and punishments. Teachers as educators must also have morals that are in accordance with the Qur’an and the characteristics of the Prophet Muhammad such as honesty, patience, self-respect, discipline and responsibility, intelligent, trustworthy, conveying, diligent in worship, respect and speak politely.